Clinicodemographic and Psychosocial Factors Related to Presentation or Severity of Delusions of Theft among Females with Amnestic Mild Cognitive Impairment and Alzheimer's Disease. Issue 3 (27th May 2022) - Inamura, Keisuke; Shinagawa, Shunichiro; Tsuneizumi, Yuri; Nagata, Tomoyuki; Tagai, Kenji; Nukariya, Kazutaka; Shigeta, Masahiro
ABSTRACT: Objectives : We examined the clinicodemographic and psychosocial factors that relate to the presentation and severity of delusions of theft among female patients with amnestic mild cognitive impairment (a-MCI) and Alzheimer's disease (AD). Methods : We enrolled a total of 177 female patients with a-MCI or AD, of whom 40 presented with delusions of theft. We compared the differences in clinicodemographic and psychosocial factors of the 40 patients (delusions of theft group) with 50 age- and Mini-Mental State Examination (MMSE)-matched controls without delusions (control group). Furthermore, we identified the factors associated with the presentation of delusions of theft using a general linear model (GLM). The severity of delusions of theft was calculated using the Neuropsychiatric Inventory Questionnaire, and correlations between the clinicodemographic and psychosocial factors were examined. Results : Between the two groups, the delusions of theft group had lower scores on the Physical Self-Maintenance Scale and instrumental activities of daily living (IADL) and higher scores on the Japanese version of the Zarit Caregiver Burden Interview (ZBI-J) than the control group. GLM analysis revealed that the IADL score was related to the presentation of delusions of theft. The severity of delusions of theft correlated with the MMSE and the ZBI-J scores in the delusions of theft group. Conclusions : The two groups had several differences regarding clinicodemographic and psychosocial factors. Furthermore, lower IADL scores were related to symptom presentation. Symptom severity correlated with cognitive functioning and caregiver burden. Clinical Implications : In the determination of treatment or care, differences in these factors should be considered.